STRATEGI HARGA DALAM SEBUAH PRODUK DI PASARAN - Abdul Wahab Syakhrani; Shella Meina Aziza; Devita Sari (Jurnal Ekonomi dan Bisnis, 2024)
Pricing strategy is one of the key elements in marketing products in a highly competitive market. This paper discusses various aspects of pricing strategies that can be used by manufacturers and marketers to achieve their business goals. This article outlines the importance of understanding the market and competition when determining prices, as well as identifying the different types of pricing strategies that can be implemented. A good understanding of consumer behavior, competitor prices, and product value is key to determining the right price. Selection of prices that not only allow the company to generate profits, but also meet customer expectations and preferences, is critical. This article also reviews the concept of pricing based on cost, demand, and position in the market. Additionally, this paper discusses various pricing strategies that can be used, such as premium pricing, discount pricing, psychological pricing, and dynamic pricing. Each of these strategies has its own advantages and disadvantages, and the selection of an appropriate strategy should be based on company goals, product characteristics, and current market conditions. Finally, this paper highlights the importance of continuous analysis and adjustment of pricing strategies. The market is always changing, and companies must be prepared to adjust their prices according to changes in the business environment. This includes monitoring competition, responding to changes in consumer demand, and adjusting pricing strategies according to the company's long-term goals. In order to achieve success in pricing strategy, companies must have deep insight into their markets, as well as skills in data analysis and understanding consumer behavior. With the right approach and careful adjustments, companies can achieve their business goals through effective pricing strategies in diverse markets.